Reframing Instructional Paradigms for Generation Alpha: From Teacher-Centered to Student-Centered Pedagogy - Febby Rizka Tamami; Aminatur Rosyidah; Moses Adeleke Adeoye (Indonesian Journal of Progressive Pedagogy, 2026)
The ongoing debate between student-centered and teacher-centered pedagogy highlights the need for evidence-based integration suited to Generation Alpha learners. This study aims to examine how student-centered, teacher-centered, and integrative instructional models influence engagement, conceptual clarity, and critical thinking skills. Using a qualitative multi-method design, data were collected over eight weeks from teachers, students, and school leaders through structured classroom observations, semi-structured interviews, and analysis of documented learning artifacts. The findings show that student-centered pedagogy increased voluntary participation, multidirectional interaction, and digital enthusiasm; teacher-centered instruction enhanced structured conceptual understanding through systematic sequencing and summarization; and the integrative model produced documented evidence of analytical reasoning, comparative evaluation, and evidence-based argumentation in student outputs. The study contributes an integrative pedagogical framework that bridges instructional paradigms. It recommends balancing structured guidance with collaborative inquiry and digital integration to optimize engagement, clarity, and the development of higher-order thinking.